2015
DOI: 10.1007/s10695-015-0156-4
|View full text |Cite
|
Sign up to set email alerts
|

Using cornstarch in microparticulate diets for larvicultured tropical gar (Atractosteus tropicus)

Abstract: Aquaculture in Mexico has been developed by the cultivation of commercial species. In Tabasco, the cultivation of native species is mainly limited by the lack of nutrition studies to support its crop profitability. Among these species is the tropical gar (Atractosteus tropicus), which has great potential for cultivation. However, the nutritional value of carbohydrates in diets for this species which contribute to improved growth and survival, have not been evalulated,. Thus, in the present investigation, isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 44 publications
5
26
3
8
Order By: Relevance
“…Differences between these results can be attributed to many factors, including differential utilization of the dietary source of carbohydrates (digestion and metabolism), level included in the diet, differences in the balance of macronutrients, complexity of the carbohydrate source [11,12] and even possible differences between egg quality between spawning batches due to the limited information on nutritional requirements of broodstock in the species. Nevertheless, the same findings of acceptance and utilization of corn starch as energy source [4] and potato starch (present study) make it clear that A. tropicus larvae show a common pattern of higher growth with increasing starch levels. Hence, differences in survival can be attributed to differences in carbohydrate solubility and limitations of the carbohydrase enzyme battery to digest different starch sources [13], in conjunction with cannibalism behavior.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Differences between these results can be attributed to many factors, including differential utilization of the dietary source of carbohydrates (digestion and metabolism), level included in the diet, differences in the balance of macronutrients, complexity of the carbohydrate source [11,12] and even possible differences between egg quality between spawning batches due to the limited information on nutritional requirements of broodstock in the species. Nevertheless, the same findings of acceptance and utilization of corn starch as energy source [4] and potato starch (present study) make it clear that A. tropicus larvae show a common pattern of higher growth with increasing starch levels. Hence, differences in survival can be attributed to differences in carbohydrate solubility and limitations of the carbohydrase enzyme battery to digest different starch sources [13], in conjunction with cannibalism behavior.…”
Section: Discussionsupporting
confidence: 80%
“…However, a combined feeding strategy (Artemia naupli, live Artemia and the experimental diets mix) was used until day 14 [3], whereas experimental feeds in the present study were used as sole feed from the time of first opening of the mouth and anus. Another study on the same species that tested corn starch as a carbohydrates source with two inclusion levels (7.4% and 15.4%), following the same feeding strategy (experimental diets offered from opening of mouth and anus) as the present study, showed comparable growth rates with those reported here, although reduced cannibalism and higher survival were reported [4]. Differences between these results can be attributed to many factors, including differential utilization of the dietary source of carbohydrates (digestion and metabolism), level included in the diet, differences in the balance of macronutrients, complexity of the carbohydrate source [11,12] and even possible differences between egg quality between spawning batches due to the limited information on nutritional requirements of broodstock in the species.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, the production of this species has been limited by the lack of studies regarding the development of specific foods that allow maximizing their growth and survival and increasing production on a commercial scale [1]. For this reason, several studies on A. tropicus have focused on maximizing the production performance of the species [2], developing balanced foods based on digestive physiology [3], and improving the growth and utilization of nutrients [4,5]. On the other hand, health impacts due to outbreaks of diseases under culture conditions generate large economic losses [6]; therefore, to reduce this impact, the use of immunostimulants could enhance the immune response and increase resistance of the organism against infectious diseases [7].…”
Section: Introductionmentioning
confidence: 99%